The Impact of Digital CRM on Destination Marketing Performance for Manado : The Role of the Informed Tourist as a Mediation Variable - Ivonne Angelic Umboh; Genesa Pinero Paragados (Jurnal Telekomunikasi dan Informatika, 2025)
This study investigates the impact of digital Customer Relationship Management (digital CRM ) on the destination marketing performance of Manado, Indonesia, with a focus on the mediating role of the informed tourist. In the context of digital advancements, digital CRM represents an opportunity for Manado to enhance relationships, personalize marketing, and increase engagement with potential tourists. The informed tourist—characterized by high engagement with digital sources and reviews—is hypothesized to mediate the relationship between digital CRM and improved destination marketing performance. A quantitative survey administered to recent visitors to Manado, coupled with structural equation modelling analysis, reveals that digital CRM positively influences destination performance and highlights the critical role of informed tourists.